PENGARUH PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA MELALUI KEDISIPLINAN SEBAGAI VARIABEL INTERVENING PT. PRIMA YUDHA SARI PERAWANG RIAU - Riansyah Regi Nanda; Samsir Samsir; Marpaung Jonnes M Rio (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The company is an organization that brings together people who are commonly referredto as employees or employees to carry out household activities for the company'sproduction. Almost all companies have the goal of maximizing profits and value for thecompany, and also to improve the welfare of owners and employees. Productivity is themain indicator for the progress of a company, so increasing productivity in all parts ofthe system is a way to increase the company's economic growth rate. This study aims toanalyze the effect of occupational safety and health programs on employee productivitythrough discipline as an intervening variable at PT. Prima Yudha Sari Perawang Riau.this research was conducted at PT. Prima Yudha Sari Perawang Riau which is located onJl. DT. Srimaraja Km. 6 - Perawang, Tualang District, Siak Regency. With 30 permanentemployees, and 80 Manpower Supporting employees, the total population is 110 byAccidental Sampling (random sampling) and using the slovin formula. So, the samples inthis study were 86 people. The data analysis technique used Partial Least Square (PLS)analysis. Based on the results of the analysis, it was found that the Occupational Safetyand Health Program had a significant positive effect on Work Productivity, WorkDiscipline had a significant positive effect on Work Productivity, the Occupational Safetyand Health Program had a significant positive effect on Work Discipline, and theOccupational Health and Safety Program had a significant positive effect on WorkProductivity. through Work Discipline as an intervening variable Keywords : Occupational Safety and Health Program (P3K), Discipline, WorkProductivity